2021
DOI: 10.3390/ijerph18147626
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Years of Potential Life Lost Due to COVID-19 in Brazil

Abstract: In November 2020, Brazil ranked third in the number of cases of coronavirus disease 2019 (COVID-19) and second in the number of deaths due to the disease. We carried out a descriptive study of deaths, mortality rate, years of potential life lost (YPLL) and excess mortality due to COVID-19, based on SARS-CoV-2 records in SIVEP-Gripe (Ministry of Health of Brazil) from 16 February 2020, to 1 January 2021. In this period, there were 98,025 deaths from COVID-19 in Brazil. Men accounted for 60.5% of the estimated 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…For instance, Quast [22]. YPLL calculations either assumed a fixed target age to which years lost is measured [16,18], or used a life table to calculate the expected remaining time (i.e., time lost) for each death [17,[19][20][21][22]. An additional limitation that poses a challenge in comparisons between countries is that the range of age groups in which deaths are grouped varies considerably from country to country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Quast [22]. YPLL calculations either assumed a fixed target age to which years lost is measured [16,18], or used a life table to calculate the expected remaining time (i.e., time lost) for each death [17,[19][20][21][22]. An additional limitation that poses a challenge in comparisons between countries is that the range of age groups in which deaths are grouped varies considerably from country to country.…”
Section: Discussionmentioning
confidence: 99%
“…An additional limitation that poses a challenge in comparisons between countries is that the range of age groups in which deaths are grouped varies considerably from country to country. Only some studies reported YPLL per 100,000 population or per death [16][17][18]21,22], or used both reported deaths and excess deaths to account for the potential undercounting [17,18], adjusted the residual life expectancy entering the YLL calculation for pre-existing conditions [15,17] or attempted to contextualize the burden of COVID-19 performing a comparison with YLL due to other diseases [18][19][20][21]. Only in one study have disability-adjusted life years (DALY) lost to COVID-19 been estimated to account for both fatal cases and years lived with disability [21].…”
Section: Discussionmentioning
confidence: 99%
“…Community spread of COVID-19 was recognized in Brazil on March 20. In the 41st SE, Brazil ranked third in the world in notified cases (5.566.049) and second in number of deaths (160.496) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 It has been acknowledged as a significant public health challenge because of human, economic and substantial losses. 2 The first case of COVID-19 in Pakistan was reported from Karachi on Feb 26, 2020, to contain and curb further spread of the disease, lockdown was instituted. 3 Over years medical education has been changed from traditional apprenticeship teaching to competency based which involves regular teaching and learning activities coupled to regular assessment.…”
Section: Introductionmentioning
confidence: 99%